Emotional intelligence and transformational leadership: The two factors affecting the nurses' performance at a general hospital in Bolaang Mongondow Monompia, Kotamobagu, Indonesia - Juritno Harmi Gaib; Fery Mendrofa; Rita Dewi (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2023)
Background: Emotional intelligence and transformational leadership are two important factors for nurses to be able to motivate themselves and build intra relationships in hospitals, and may affect to the nurses' performance. Aims: The purpose of the study was to determine how emotional intelligence and leadership affecting the nurses' performance at the General Hospital of the Evangelical Masehi Church, Bolaang Mongondow Monompia, Kotamobagu, Indonesia Methods: This original research employed an analytic observational with a quantitative approach and a cross sectional study design. A set of questionnaires was distributed to the participated nurses to define the respondents' characteristics, emotional intelligence (10 questions), leadership transformation (12 questions), and the nurses' performances (8 questions). A total of 48 nurses were selected in August 2022 using a total sampling technique, and their answers were included to the further statistical analysis using PSS software version 15. Results: Not different with other hospitals, at the Regional General Hospital of Kotamobagu the majority of nurses was female, and relatively has worked for more than 5 years. It has been noted that the nurses were measured with sufficient emotional intelligence (43.8%), transformational leadership (54.1%), and performances (58.3%). However, the number of nurses having poor emotional intelligence and performance were relatively high, respectively at 12.4% and 14.6%. It is indicated that the nurses performance were significantly resulted by the two factors: Emotional intelligence (p-value: 0.025) and transformational leadership (p-value: 0.005). Conclusion: This study concludes that the emotional intelligence and transformational leadership are moderating variables to strengthen the nurses' performance. This study noted that the higher number of nurses highly perform if having good emotional intelligence and good transformational leadership. Therefore, it is recommended to pay attention to the two strong indicators from this study if a hospital manager plans to improve the nurses' performance.